PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAANDALAM MENINGKATKAN PROFITABILITAS - Ardianti .; Abid Ramadhan (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2020)
Corporate social responsibility or more popularly with the term corporate social responsibility is a concept in which a company cannot be separated from its relationship with stakeholders or stakeholders. This concept combines social and economic aspects which aim to help create prosperity for company stakeholders such as consumers, the environment and the surrounding community. The purpose of this study is to analyze and reveal the effect of CSR on profitability as calculated by Return on Assets in companies listed on the Jakarta Islamic Index (JII). model of research is quantitative in nature. Methods of data analysis in this study using simple linear regression analysis method. The study population came from companies registered in JII with an observation period from 2013-2018 with the annual report as a research study material. The results of the study showed that CSR had no effect on ROA.